Does compliance with healthy lifestyle behaviours cluster within individuals in Australian primary school‐aged children?. (23rd July 2017) - Olds, T.; Sanders, I.; Maher, C.; Fraysse, F.; Bell, L.; Leslie, E.
Abstract: Background: The 3 "movement behaviours" of sleep, screen time, and physical activity are associated with a wide range of health outcomes in children. This study examined whether these behaviours cluster together within individuals in Australian primary school children. Methods: Three datasets including 4, 449 9‐ to 11‐year‐old children were interrogated—(a) Obesity Prevention and Lifestyle (OPAL), (b) the International Study of Children, Obesity, Lifestyle and Environment (ISCOLE), and (c) the National Children's Nutrition and Physical Activity Survey (NCNPAS). The surveys measured movement behaviours using different instruments (accelerometry, use of time recall, and questionnaires) and different operationalizations of compliance. Observed frequencies of compliance with various combinations of guidelines were compared with expected frequencies based on the assumption of independence, using chi‐square tests. Results: Compliance with the sleep guidelines was relatively high (72%, 75%, and 79% in the OPAL, ISCOLE, and NCNPAS datasets, respectively), and compliance with the screen (18%, 35%, and 22%) and physical activity (33%, 57%, and 87%) guidelines was generally lower. Against expectation, there was no evidence of clustering in any of the datasets ( p  > .99). Conclusions: Compliance with movement behaviour guidelines does not cluster within individuals in 9‐ to 11‐year‐old Australian children. It may be unlikely that fostering compliance with one guideline will have a flow‐on effect to the others. Temporal trade‐offs (i.e., the need to choose one movement behaviour above another) in the 24‐hr day may contribute to the lack of clustering.